Can Capsicum spp. genotypes resist simultaneous damage by both Phytophthora capsici and Bemisia tabaci? Can natural enemies of Bemisia complement plant resistance? - Corozo-Quiñónez, Liliana; Chirinos, Dorys T.; Saltos-Rezabala, Luis; Monteros-Altamirano, Alvaro (Frontiers in Ecology and Evolution, 2024)
Capsicum (Solanaceae) includes peppers and chilies. Phytophthora capsici (Peronosporaceae) and Bemisia tabaci (Hemiptera: Aleyrodidae) are two relevant problems in the production of this genus. Among the sustainable alternatives for disease and pest control, plant resistance and biological control stand out. The main objective of this research was to evaluate the resistance of Capsicum genotypes to damage by P. capsici and infestation by B. tabaci, as well as to diagnose whether the action of predators and parasitoids against B. tabaci could complement the resistance of the plants. The progression of disease caused by P. capsici and infestation by B. tabaci was estimated in 23 Capsicum genotypes, corresponding to the species: Capsicum annuum, Capsicum baccatum, Capsicum chinense, Capsicum frutescens and C. pubescens, from the GenBank of the National Institute of Agricultural Research (INIAP-Ecuador). Three genotypes: ECU-11993 (C. baccatum), ECU-11991 and ECU-2244 (C. pubescens) showed high susceptibility to both P. capsici damage and B. tabaci infestation. C. baccatum, C. chinense and C. frutescens genotypes showed the highest resistance to both pests, suggesting multiple resistance. Six taxa of predators and parasitoids reduced B. tabaci populations that developed in the most infested genotypes. Plant resistance is a control alternative that could allow the use of biological control, making it environmentally friendly. These results provide the basis for breeding programs in Capsicum.